Esterification of High Free Fatty Acid Jatropha curcas Oil for Biodiesel Production - Abdelrahman, Maha A. A.; Yassin, Atif A. A.; Hussein, Ismail Hassan; Karama, Abdallah B.; Mirghani, Mohamed E.S. (Gezira Journal of Engineering and Applied Sciences, 2020)
This study investigated the esterification of high free fatty acid (FFA) Jatropha curcas ( J. curcas ) seed oil (6.3 to14.6 %) to produce biodiesel using sulphuric acid with reaction parameters 1% H 2 SO 4 , 600 rpm at 60 o C and one hour reaction time. At methanol to oil ratio 3:1, FFAs were reduced to 4.73% with conversion 45%; at 6:1 methanol to oil ratio, FFAs were reduced to 2.31% with conversion 72%; at 7.5:1 methanol to oil ratio FFAs are decreased to less than 2% with conversion ≥85% and there is no considerable difference when increasing methanol to oil ratio to 9:1. Hence the optimum methanol to oil molar ratio is 7.5:1, moreover, the esterification process is not affected by the initial FFA.